Stomatal Responses to Light, CO2, and Mesophyll Tissue in Vicia faba and Kalanchoë fedtschenkoi - Santos, Mauro G.; Davey, Phillip A.; Hofmann, Tanja A.; Borland, Anne; Hartwell, James; Lawson, Tracy (Frontiers in Plant Science, 2021)
Using Vicia faba (C3) and Kalanchoë fedtschenkoi (Crassulacean acid metabolism; CAM), the responses of stomatal aperture to light and CO2 were studied in material sampled from both light and dark periods. Direct comparison was made between intact leaf segments, epidermes grafted onto exposed mesophyll, and isolated epidermal peels, including transplantations between species and between diel periods. We report here stomatal opening in response to darkness in isolated CAM peels from the light period, but not from the dark. Furthermore, we show that C3 mesophyll can stimulate CAM stomata in transplanted peels to behave as C3 in response to light and CO2. By using peels and mesophyll from plants sampled in the dark and the light period, we provide clear evidence that CAM stomata behaved differently to C3. This may be linked to stored metabolites/ ions and signalling pathway components within the guard cells, and/or a mesophyll derived signal. Overall our results provide evidence for both the involvement of guard cell metabolism and mesophyll signals in stomatal responses in both C3 and CAM species.